Patterns of Bat Diversity in an Undisturbed Forest and Forest Mosaic Habitats of the Afromontane Forest Biome of Western Cameroon - BakwoFils, Eric-Moîse; Mongombe, Manga Aaron; Manfothang, Dongmo Ervis; Gomeh-Djame, Aicha; Takuo, Jean Michel; Bilong, Bilong Charles Felix (Frontiers in Ecology and Evolution, 2021)
Anthropogenic activities continue to degrade natural montane ecosystems globally. Bats are among the group of organisms most sensitive to these changes. We analyzed how bats are affected by human-induced habitat changes by comparing bat species diversity and functional diversity in an undisturbed forest habitat and a disturbed mosaic forest habitat of the Afromontane biome of Cameroon. We recorded 244 individuals from 13 species in the undisturbed forest, while 233 individuals from 16 species were recorded in the disturbed forest. Bat diversity was higher in disturbed habitats (D = 0.84) than undisturbed habitats (D = 0.67). Jackknife 1 species richness estimator suggests 21.53 species for the disturbed forest and 19.30 for the undisturbed forest. Closed-space forager insectivorous bats made up nearly half of the species in the undisturbed forest, but this dropped to 25% in the disturbed forest, meanwhile, edge-space foragers increased in the disturbed forest. Bat community analyses by ordination revealed a distinct bat community composition between the two forest types, demonstrated as a significant difference in diversity between the two forest types. The distribution of Rousettus aegyptiacus, Myonycteris angolensis, Hipposideros cf. ruber, and Micropteropus pusillus contribute the most to the difference in bat community composition between the two forest types. Edge and open-space species were likely to benefit from additional resources provided by the disturbed area, by expanding their range and distribution. However, this may not compensate for the potential risk of local extinction of forest species caused by the loss of pristine forest, thus measures to conserve montane forest remnants should be of utmost significance. Keywords: Edge species, bats, Human activities, Undisturbed forest, Disturbed forest